Diagnostic Role of Contrast-Enhanced Ultrasound (CEUS) in Characterizing Indeterminate Liver Lesions - JODAD, DR; ALI, MUMTAZ; SAEED, ANAS (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Indeterminate lesions of the liver are commonly detected in abdominal imaging and in most instances they are cause of diagnostic ambiguity when traditional ultrasound, CT, or MRI fails to clearly define them as benign or malignant. Contrast-Enhanced Ultrasound (CEUS) has become a promising, real-time imaging modality, which does not expose ionizing radiation or any exposure of nephrotoxic contrast to visualize the microvascular perfusion. It is especially useful in the assessment of hepatic lesion evaluation because of its capacity to show characteristic enhancement and a wash-out effect. Objectives: The objective of the study was to assess the diagnostic utility of CEUS as a tool to characterize indeterminate liver lesions as well as compare patterns of its improvement with ultimate diagnosis made using CT/MRI, histopathology, or imaging follow-up. Methods: The study was a cross-sectional diagnostic accuracy study, which was carried out among tertiary care hospitals in Punjab, Pakistan between June 2024 and May 2025. There were 80 adult patients with unspecified hepatic lesions identified after the first grayscale imaging who were enrolled. Secondary generation microbubble contrast agent was used to perform the CEUS and a lesion was evaluated at the arterial, portal venous and late stages. Behavioral enhancements, wash-in behavior, wash-out behavior and perfusion were studied. Contrast-enhanced CT/MRI, biopsy or 6-month follow-up imaging were used to confirm the final diagnoses. Results: CEUS correctly detected 47 out of 52 benign lesions and 26 out of 28 malignant lesions and had a diagnostic accuracy of 91.2 with high sensitivity (92.8) and specificity (90.4). Typical patterns in persistent or isoenhancing late phase were observed in benign lesions (hemangiomas and focal nodular hyperplasia). Malignant lesions such as hepatocellular carcinoma and metastases showed hyperenhancement of the arteries and then early or late wash-out. Conclusion: CEUS is an effective, safe, cost effective modality, which can distinguish between benign and malignant liver lesions. It can play a crucial role in eliminating unnecessary biopsies and supplement CT/MRI in routine liver examination, since its application in diagnostic algorithms can greatly decrease the number of unnecessary biopsies.